Monolayer Graphene Coating of Intracortical Probes for Long‐Lasting Neural Activity Monitoring. Issue 18 (12th August 2019) - Bourrier, Antoine; Shkorbatova, Polina; Bonizzato, Marco; Rey, Elodie; Barraud, Quentin; Courtine, Gregoire; Othmen, Riadh; Reita, Valerie; Bouchiat, Vincent; Delacour, Cécile
Abstract : The invasiveness of intracortical interfaces currently used today is responsible for the formation of an intense immunoresponse and inflammatory reaction from neural cells and tissues. This leads to a high concentration of reactive glial cells around the implant site, creating a physical barrier between the neurons and the recording channels. Such a rejection of foreign analog interfaces causes neural signals to fade from recordings which become flooded by background noise after a few weeks. Despite their invasiveness, those devices are required to track single neuron activity and decode fine sensory or motor commands. In particular, such quantitative and long‐lasting recordings of individual neurons are crucial during a long time period (several months) to restore essential functions of the cortex, disrupted after injuries, stroke, or neurodegenerative diseases. To overcome this limitation, graphene and related materials have attracted numerous interests, as they gather in the same material many suitable properties for interfacing living matter, such as an exceptionally high neural affinity, diffusion barrier, and high physical robustness. In this work, the neural affinity of a graphene monolayer with numerous materials commonly used in neuroprostheses is compared, and its impact on the performance and durability of intracortical probes is investigated. For that purpose, an innovative coating method to wrap 3D intracortical probes with a continuous monolayer graphene is developed. Experimental evidence demonstrate the positive impact of graphene on the bioacceptance of conventional intracortical probes, in terms of detection efficiency and tissues responses, allowing real‐time samplings of motor neuron activity during 5 weeks. Since continuous graphene coatings can easily be implemented on a wide range of 3D surfaces, this study further motivates the use of graphene and related materials as it could significantly contribute to reduce the current rejection of neural probes currently used in many research areas, from fundamental neurosciences to medicine and neuroprostheses. Abstract : An innovative coating method is reported to wrap intracortical probes with continuous graphene monolayers, in order to investigate its impact on the bioacceptance of the implants. Experimental evidence show that the graphene coating significantly lowers the immune response and enhances the performance and the durability of the probes, paving the way for long‐term reliable recordings of individual motor neurons.